Faktor Yang Berhubungan Dengan Kelelahan Kerja Pada Petani Rumput Laut Di Kelurahan Tanjung Harapan - Syafiq, Muhammad; Nurgahayu; Ella Andanie (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Work fatigue is when a person experiences a decline in physical and mental condition due to heavy and continuous work activities. Seaweed farming is a job with high work intensity, such as the harvesting stage, which is carried out above the water surface and exposed to sunlight. This condition can impact productivity, work quality, and worker health. The research used a quantitative approach with a cross-sectional design. This study aims to determine fatigue-related issues in seaweed farmers in Tanjung Harapan Village. Based on the study's results, no statistically significant relationship was found between health status and the level of work fatigue, indicated by a p-value of 0.056. Work duration with the level of work fatigue (p = 0.03) showed a relationship, as did the intensity of the workload with the level of fatigue felt by workers (p = 0.02). Meanwhile, nutritional status did not show a significant relationship with the level of work fatigue. (p = 0.687). Based on the study results, it can be concluded that health status and nutritional status have no relationship with work fatigue, while work duration and workload have a relationship with work fatigue.